Males at High Risk for Breast Cancer: Who Are They and How Should We Screen Them? - Swergold, Natalie; Murthy, Vijayashree; Chamberlain, Ronald S. (Scientific Research, 2014)
Background: It is estimated that 2240 males in the United States will develop invasive breast cancer (BC) in 2013, resulting in 410 deaths. Overall, male breast cancers (MBCs) are diagnosed with larger tumor size, more frequent lymphatic invasion, and advanced tumor stage compared to their female counterparts. Several risk factors have been elucidated for the development of MBC, and this paper aims to critically review the existing literature on at-risk populations and provide screening recommendations. Methods: A comprehensive search for all published studies on populations at risk for MBC using PubMed, EBSCOhost, and Google Scholar was performed (1982- 2013). The search focused specifically on genetic and epidemiologic risk factors, and screening for MBC. Keywords searched included “male breast cancer risk factors”, “male breast cancer epidemiology”, and “male breast cancer genetics”. A total of 34 studies involving 4,865,819 patients were identified. Results: Five studies (N = 327,667) focused primarily on family history of breast cancer as a risk factor for MBC. 15% - 20% of men with BC have a family history of breast or ovarian cancer, and a family history of BC among first-degree relatives confers a 2- to 3-fold increase in MBC risk (odds ratio = 3.3). Seventeen studies (N = 5451) analyzed associations between several heritable genes and MBC. Lifetime MBC risk among BRCA1 mutation carriers is 1% - 5%, while MBC risk in BRCA2 mutation carriers is higher and varies between 4% - 40%. Less clear associations between MBC and PALB2, Androgen Receptor gene, CYP17, and CHEK2 mutations have also been documented. Five studies (N = 16,667) have addressed occupational risk factors for MBC. An 8-fold increase in MBC is reported in males working in the cosmetic cream manufacturing, and the motor vehicle industries. A meta-analysis of 18 trials also identified electromagnetic field exposure as a potential MBC risk, though causation remains undocumented. Eleven studies (N = 4,843,598) analyzed the role of abnormalities in the androgen-to-estrogen ratio as a risk factor for MBC. Conditions associated with increased MBC risk include Klinefelter’s syndrome (relative risk, RR = 29.64), obesity (RR = 1.98), orchitis/epididymitis (RR = 1.84), and gynecomastia (RR = 5.86). Conclusion: Routine screening for MBC should be considered in all high risk male populations, including those with a prior history of breast carcinoma, a strong family history of BC (defined as an affected mother or sister), a positive BRCA2 mutation status (regardless of family history), and men diagnosed with Klinefelter’s syndrome, or those in the chemical or motor vehicle industries. Genetic testing for BRCA2 should be recommended for all MBC patients. Increased public and physician education on MBC is necessary to raise awareness about this rare disease and the need for screening of at-risk populations.
Keywords: Male Breast Cancer Risk Factors; Carcinoma of the Male Breast; Breast Carcinoma